HealthTalks - Improving Health Communication and Personal Information Management - João Miguel Lopes Vale Cardoso Monteiro (2017)
An individual's health condition depends on themselves and their health professional, but both are fallible. A patient's health literacy, which is their ability to obtain and use health information, has a direct impact on their health, as do their personal health information management proficiency and their relationship with their physician. However, half of the Portuguese population has problematic or inadequate levels of health literacy. At the same time, 84% of U.S.A. patients verify the veracity of their physician's assertions after an appointment, which may jeopardise their trust in their doctors and, by extension, their treatment. Finally, information management methods sometimes fail due to human error such as recording information incorrectly, or making mistakes and omissions. These are some of the hindrances to a good healthcare that patients currently face. Since those aspects are not well documented in our region, we created a questionnaire in collaboration with a doctor and proceeded to examine Porto residents in order to better characterise this population and their needs. The survey was made available online to quickly gather a lot of valid responses, but we also asked for permission to distribute printed copies in São João Hospital Centre to target a broader and more representative population. We decided to tackle some of the aforementioned faults in the patients' healthcare by developing HealthTalks. It is a mobile app that empowers the patients with tools that may ease their day-to-day health tasks and self-care ability. It does so by enabling a better personal health information management and promoting a more straightforward communication between patient and physician, while giving information about the health topics they discuss. This is accomplished by recording a medical consultation, transcribing its dialogue, giving more information about used medical terms, and allowing all that information to be easily managed by the patient. Even though the app is meant for the general adult Portuguese population, extensive usability tests with full demographic representation were not feasible, so we conducted those tests with elderly users. This is a target group that is expected to benefit greatly from this solution, while at the same time assumed to be less receptive to it. These tests allowed us to define and rethink some aspects related to HealthTalks' interface and user experience. There were several options of speech recognition software to implement, which were narrowed to two after comparing their characteristics: Google Cloud Speech API and Bing Speech API. Those options were tested with generalist and medical texts so that we could make an informed final decision on which to use. Our choice was Google Cloud Speech API, since it consistently showed better results than the latter. After its development, the app's performance was also evaluated to understand its applicability in a real-world scenario. That evaluation was mainly focused on the quality of the transcription, since the definition of terms depends on it being accurate in order to correctly identify medical terminology. In the future, our goal is to simulate consultations to better reproduce their real conditions, and talk extensively with physicians so as to better understand their perspective on the problems previously mentioned and HealthTalks' approach to tackling them.